Genome sequencing of deep-sea hydrothermal vent snails reveals adaptions to extreme environments. Issue 12 (15th December 2020) - Zeng, Xiang; Zhang, Yaolei; Meng, Lingfeng; Fan, Guangyi; Bai, Jie; Chen, Jianwei; Song, Yue; Seim, Inge; Wang, Congyan; Shao, Zenghua; Liu, Nanxi; Lu, Haorong; et al.
Abstract: Background: The scaly-foot snail ( Chrysomallon squamiferum ) is highly adapted to deep-sea hydrothermal vents and has drawn much interest since its discovery. However, the limited information on its genome has impeded further related research and understanding of its adaptation to deep-sea hydrothermal vents. Findings: Here, we report the whole-genome sequencing and assembly of the scaly-foot snail and another snail ( Gigantopelta aegis ), which inhabits similar environments. Using Oxford Nanopore Technology, 10X Genomics, and Hi-C technologies, we obtained a chromosome-level genome of C. squamiferum with an N50 size of 20.71 Mb. By constructing a phylogenetic tree, we found that these 2 deep-sea snails evolved independently of other snails. Their divergence from each other occurred ∼66.3 million years ago. Comparative genomic analysis showed that different snails have diverse genome sizes and repeat contents. Deep-sea snails have more DNA transposons and long terminal repeats but fewer long interspersed nuclear elements than other snails. Gene family analysis revealed that deep-sea snails experienced stronger selective pressures than freshwater snails, and gene families related to the nervous system, immune system, metabolism, DNA stability, antioxidation, and biomineralization were significantly expanded in scaly-foot snails. We also found 251 H-2 Class II histocompatibility antigen, A-U α chain-like ( H2-Aal ) genes, which exist uniquely in the Gigantopelta aegis genome. This finding is important for investigating the evolution of major histocompatibility complex (MHC) genes. Conclusion: Our study provides new insights into deep-sea snail genomes and valuable resources for further studies.